Group investigation technique for better reading comprehension skill - Chairina Nasir; A. Gani Sofyan; Dina Haqqini (Universitas Syiah Kuala, 2019)
This study was conducted to investigate the effect of using Group Investigation Technique (GIT) in teaching reading comprehension at the second grade class of a junior high school in Banda Aceh and to identify the most difficult reading comprehension aspect that students at that level faced. An experimental design was used and the data were collected through tests as so for the instruments. There were two tests, namely pre-test, and post-test, applied in the form of multiple-choice questions. The population of this study was all of the second-grade students. Then, two classes were randomly chosen as the samples: experimental class and controlled class. The findings indicated that there was an improvement in students' achievement in the experimental class. The study applied gain-score calculation in which the mean for the experimental class was 0.57, while the controlled class was 0.22. The researchers also used the t-test to prove the hypotheses. The result showed that t-scoret-table or 34.761.68, which means the H1 is accepted and H0 is rejected. To conclude, the students who were taught reading comprehension by using GIT achieved significant improvement. Besides, after the determination of the mean of the post-test and pre-test scores which were divided into four aspects of reading comprehension: main idea (MI), vocabulary (V), detailed information (DI), and reference (R), the result showed that MI=25.91, V=28.64, DI=25.00, and R=31.59. Therefore, it was found that the most difficult aspect of reading comprehension was detailed information (DI. Meanwhile, time management becomes a paramount concern in implementing the GIT due to its nature of complexity.